2022
DOI: 10.1073/pnas.2212930119
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome composition modulates secondary metabolism in a multispecies bacterial community

Abstract: Bacterial secondary metabolites are a major source of antibiotics and other bioactive compounds. In microbial communities, these molecules can mediate interspecies interactions and responses to environmental change. Despite the importance of secondary metabolites in human health and microbial ecology, little is known about their roles and regulation in the context of multispecies communities. In a simplified model of the rhizosphere composed of Bacillus cereus , Flavobacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 67 publications
2
27
0
Order By: Relevance
“…In agreement with other studies (Chevrette et al, 2022), RNA-Seq analysis revealed that the two microorganisms perceived the presence of each other in the in vitro co-culture (3 days after the co-inoculation), as evidenced by the reprogramming of both transcriptomes, compared to the single cultures. It could be argued that the transcriptome changes of AtB-42 (887 DEGs out of 2613 genes) were the result of the growth inhibition due to the presence of M10.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with other studies (Chevrette et al, 2022), RNA-Seq analysis revealed that the two microorganisms perceived the presence of each other in the in vitro co-culture (3 days after the co-inoculation), as evidenced by the reprogramming of both transcriptomes, compared to the single cultures. It could be argued that the transcriptome changes of AtB-42 (887 DEGs out of 2613 genes) were the result of the growth inhibition due to the presence of M10.…”
Section: Discussionsupporting
confidence: 91%
“…However, studies of microbial co-culture have achieved the use of more than two microorganisms in one culture system. Indeed, Chevrette and co-workers have discovered that the abundance of transcripts of BGCs and the metabolic profiles differ between monocultures, dual-cultivation, and a tripartite community and that the dynamics of specialized metabolism depend on the interspecies interactions and the community species composition ( Chevrette et al, 2022 ). To exemplify these dynamics, Pettit and co-workers have simultaneously co-cultured five fungi ( Ovadendron sulphureoochraceum , Ascochyta pisi , Emericellopsis minima , Cylindrocarpon destructans , and Fusarium oxysporum ) for the biosynthesis of potential antineoplastic substances.…”
Section: Microorganisms In Mixed Culturesmentioning
confidence: 99%
“…7 The dominance of Proteobacteria and Actinobacteria in termite mound soils from this study supported this fact as some strains ( Bacillus, Pseudomonas and Streptomyces species) from Proteobacteria and Actinobacteria are recognized to synthesize almost 80% of the total metabolites identified nowadays. 30,31 It has also been established that well-known antimicrobial compounds like streptothricin, actinomycin, and streptomycin, which are of agricultural significance, are produced by some species of the Actinobacteria , 32 which was very abundant in termite mound soils from this study.…”
Section: Discussionmentioning
confidence: 55%
“…33 Our study revealed a lot of pathways and genes that code for secondary metabolism (Figure 3 and Supplemental Table S3), a unique characteristic of microorganisms to synthesize a variety of metabolites that are significant for self-defense. 32 They also play huge function in microbe–microbe, host–microbe, and microbe–environment collaborations. 34 The presence of genes linked to auxin biosynthesis (a growth regulator influencing the cell elongation and division in plants) in our study shows that termite mound soil housed auxin-producing and auxin-secreting microbiome.…”
Section: Discussionmentioning
confidence: 99%